Handbook of research on entrepreneurship in agriculture and rural development - Alsos, Gry Agnete (Cheltenham, UK : Edward Elgar, 2011)
This unique and path-breaking handbook draws together the best current research in the area of entrepreneurship in agriculture, food production and rural development.
Includes bibliographical references and index.
rua 26/04/13, ijb 21/02/2019
Loans
Keywords: Agricultural development projects; Rural development projects; Entrepreneurship